Earth Pressure of Three-Dimensional Stress States under Different Strength Criteria and Its Application. (15th September 2021) - Zhang, Yu; Liu, Jin; Fan, Te-Jia; Xu, Chen-Yang; Meng, Tian-Yi; Zhao, Yang; Su, An
Abstract : To solve the Earth pressure problems in practical engineering, such as retaining walls and foundation pits, we derive active and passive Earth pressure formulas in accordance with the relationship between intermediate principal stress and excavation under three-dimensional stress states. The formulas are derived on the basis of the Mohr–Coulomb, spatially mobilized plane (SMP), σ 3 SMP, Lade–Duncan, axisymmetric compression- (AC-) SMP strength, and generalized Mises (Gen-Mises) criteria and then extended to clay. We also compare the calculated Earth pressure with the measured data. Results indicate that the Earth pressure considering medium principal stress contribution under a three-dimensional stress state is consistent with the actual engineering. The calculated active Earth pressure in the Mohr–Coulomb strength criterion is larger, and the passive Earth pressure is smaller than the practical one because the intermediate principal stress effect is not considered. The calculated results of the SMP, σ 3 SMP, Lade–Duncan, AC-SMP strength, and Gen-Mises criteria are close to the measured data, among which the result of the Gen-Mises criterion is closer. The Earth pressure calculated using the Lade–Duncan criterion is no longer appropriate to describe the Earth pressure under medium principal stress condition in this study. The results of this study have theoretical significance for retaining structure design under a three-dimensional stress state.